If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 + c = -17 Solving 19 + c = -17 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + c = -17 + -19 Combine like terms: 19 + -19 = 0 0 + c = -17 + -19 c = -17 + -19 Combine like terms: -17 + -19 = -36 c = -36 Simplifying c = -36
| 80000=0.7x+17000 | | v-1*1/3=1*4/5 | | 24z^3=20z^2+84z | | 28=10t | | 2=r^12 | | 4u-17=27 | | 3x=1*1/2 | | 2(logx)=-1 | | g-2/=-8 | | 8-42w=16 | | 4+2q-(3q+9)-(5q+8)= | | 75=6v | | 2(c+x)=3x | | x/2=13x | | n/.f=n/81 | | 1200x+500=24 | | 4x-17=-45 | | 8x^3-2x+24=0 | | 4(3a-4)=4(5a-20) | | -4/32= | | 4(k-1)+3=2(k+5) | | 68+46+12-6=180 | | 1.5x-5.5=3/2x-1.2 | | 3/4*x=1/8 | | 3b+n=30 | | -1/4c=-20 | | sqrt(3x+19)-sqrt(x+2)=3 | | 1.5x-0.5=3/2x-1.2 | | 28/25--20= | | 2.2x+3.5=3y | | 2x-3/2=0 | | (x-4)^3/2 |